2018
DOI: 10.1038/s41598-018-22894-6
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of Potent, Insecticidal Synthetic Mimics of the Spinosyn Macrolide Natural Products

Abstract: New insect pest control agents are needed to meet the demands to feed an expanding global population, to address the desire for more environmentally-friendly insecticide tools, and to fill the loss of control options in some crop-pest complexes due to development of insecticide resistance. The spinosyns are a highly effective class of naturally occurring, fermentation derived insecticides, possessing a very favorable environmental profile. Chemically, the spinosyns are composed of a large complex macrolide tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…However, unlike other NPs, commercially viable synthetic mimics of the large macrolides have been unknown for agrochemicals and, as far as can be determined, pharmaceuticals. We recently reported that simplified synthetic mimics of the complex spinosyn structure are indeed possible, exhibiting laboratory efficacy near that of spinetoram . Herein we provide further elaboration on the discovery and development of synthetic spinosyn mimics, resulting in highly active, photostable analogs that demonstrate excellent in vivo efficacy in the laboratory and field.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, unlike other NPs, commercially viable synthetic mimics of the large macrolides have been unknown for agrochemicals and, as far as can be determined, pharmaceuticals. We recently reported that simplified synthetic mimics of the complex spinosyn structure are indeed possible, exhibiting laboratory efficacy near that of spinetoram . Herein we provide further elaboration on the discovery and development of synthetic spinosyn mimics, resulting in highly active, photostable analogs that demonstrate excellent in vivo efficacy in the laboratory and field.…”
Section: Introductionmentioning
confidence: 90%
“…Structures of commercial insecticides, spinosad 1 and spinetoram 4 , and a conceptual route to the discovery of the synthetic spinosyn mimics. Spinosyn mimics were synthesized as described by Crouse et al …”
Section: Design Of Synthetic Spinosyn Mimicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the NP-based discovery program at Corteva has continued to deliver new crop protection compounds, including the new fungicides fenpicoxamid 33,34 and florylpicoxamid 7 and the new insecticidal synthetic spinosyn mimics. 35,36 As noted above, a key advantage of an NP-based discovery program is the enhanced probability of finding crop protection compounds that possess new MoAs. This outcome is exemplified by both the spinosyns and new fungicidal chemistry, and it has further served to maintain interest in NP-based lead generation within CAS.…”
Section: Introductionmentioning
confidence: 99%
“…Along the way, the discovery a new family (21‐butenyl) of spinosyns and the genetic engineering of the spinosyn biosynthetic pathway to produce new spinosyn derivatives have also helped maintain interest in NPs. More recently, the NP‐based discovery program at Corteva has continued to deliver new crop protection compounds, including the new fungicides fenpicoxamid and florylpicoxamid and the new insecticidal synthetic spinosyn mimics . As noted above, a key advantage of an NP‐based discovery program is the enhanced probability of finding crop protection compounds that possess new MoAs.…”
Section: Introductionmentioning
confidence: 99%